Management of anticoagulation in hip fractures: A pragmatic approach. Issue 9 (21st September 2017) - Yassa, Rafik; Khalfaoui, Mahdi Yacine; Hujazi, Ihab; Sevenoaks, Hannah; Dunkow, Paul
Abstract : Hip fractures are common and increasing with an ageing population. In the United Kingdom, the national guidelines recommend operative intervention within 36 hours of diagnosis. However, long-term anticoagulant treatment is frequently encountered in these patients which can delay surgical intervention. Despite this, there are no set national standards for management of drug-induced coagulopathy pre-operatively in the context of hip fractures. The aim of this study was to evaluate the management protocols available in the current literature for the commonly encountered coagulopathy-inducing agents. We reviewed the current literature, identified the reversal agents used in coagulopathy management and assessed the evidence to determine the optimal timing, doses and routes of administration. Warfarin and other vitamin K antagonists (VKA) can be reversed effectively using vitamin K with a dose in the range of 2 mg to 10 mg intravenously to correct coagulopathy. The role of fresh frozen plasma is not clear from the current evidence while prothrombin complex remains a reliable and safe method for immediate reversal of VKA-induced coagulopathy in hip fracture surgery or failed vitamin K treatment reversal. The literature suggests that surgery should not be delayed in patients on classical antiplatelet medications (aspirin or clopidogrel), but spinal or regional anaesthetic methods should be avoided for the latter. However, evidence regarding the use of more novel antiplatelet medications (e.g. ticagrelor) and direct oral anticoagulants remains a largely unexplored area in the context of hip fracture surgery. We suggest treatment protocols based on best available evidence and guidance from allied specialties. Hip fracture surgery presents a common management dilemma where semi-urgent surgery is required. In this article, we advocate an evidence-based algorithm as a guide for managing these anticoagulated patients. Cite this article: EFORT Open Rev 2017;2:394–402. DOI: 10.1302/2058-5241.2.160083